Implementing (K, Na)NbO3-based lead-free ferroelectric films to piezoelectric micromachined ultrasonic transducers. (1st December 2022) - Huang, Yu; Shu, Liang; Hu, Fade; Liu, Lisha; Zhou, Zhen; Cheng, Yue-Yu-Shan; Zhang, Suwei; Li, Wei; Li, Qian; Wang, Hongliang; Dong, Zhinan; Wei, Liyu; et al.
Abstract: Piezoelectric micromachined ultrasonic transducers (pMUTs) have attracted widespread attentions on account of their vital applications in medical imaging, fingerprint identification, range-finding, gesture recognition, and so on . The piezoelectric layer, which is the key component for pMUTs, has been dominated by ferroelectric Pb(Zr, Ti)O3 (PZT) because of its outstanding piezoelectric performance, especially in the case of pMUT transmitters. However, the toxicity of lead restricts their medical-related applications, so developing lead-free pMUTs should be of great significance but remains challenging. As a precedent, the present work pioneered the processing of lead-free (K, Na)NbO3 (KNN)-based pMUTs, and obtained an ultrahigh transmitting sensitivity of 1250 nm V −1 at 66.2 kHz, which is superior to the majority of PZT-based pMUTs reported so far. The excellent displacement sensitivity can be ascribed to the dense and homogeneous feature, (100)-textured structure, orthorhombic-tetragonal phase coexistence, nanosized domains, great electrical insulation and high piezoresponse of the KNN-based film as well as the the elaborate micromachining process. This work initiated a successful precedent for applying lead-free ferroelectric films to pMUTs also as a breakthrough step in promoting KNN-based films toward practical applications. Graphical Abstract: ga1 Highlights: Lead-free ferroelectric film has been first integrated into piezoelectric micromachined ultrasonic transducers. An ultrahigh transmitting sensitivity of 1250 nm V −1 was achieved in KNN-based pMUTs, being comparable to Pb-based ones. The high-performance origin of the KNN-based pMUTs is discussed in terms of film properties and device designs.